2(f-8)=-2

Simple and best practice solution for 2(f-8)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(f-8)=-2 equation:


Simplifying
2(f + -8) = -2

Reorder the terms:
2(-8 + f) = -2
(-8 * 2 + f * 2) = -2
(-16 + 2f) = -2

Solving
-16 + 2f = -2

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + 2f = -2 + 16

Combine like terms: -16 + 16 = 0
0 + 2f = -2 + 16
2f = -2 + 16

Combine like terms: -2 + 16 = 14
2f = 14

Divide each side by '2'.
f = 7

Simplifying
f = 7

See similar equations:

| 9x-94=116-5x | | 5w+16=66 | | .5b^2-81=0 | | 1.3x=-13 | | -3x+17+5x-7=-5x+2+7x-10 | | 3x+10=33+2x | | 0.5-3-x=6.5 | | -5+5u=-10 | | Y^2-4y-x=0 | | 3(2l+7)=63 | | 5-(a-4)=-2x+1 | | 8a-a=7a-6 | | 10(s-4)=-83 | | 2x+8+7+8x=4x+20+x+5 | | x^2+3x=304 | | 2(7x+2)+6=14x-10 | | -4[4-(3b+4)]=5-4(3b+8) | | 3(t-1)=9t | | -(c-20)=-2 | | x=6y-2x-9 | | x^4+3x^3+9x^2+27x=0 | | 7x+3-4x+15=6x+20-3x-2 | | x=gy-2x-9 | | U=2(8n+34)+7(n+1) | | 3x+4y+360=0 | | a^2+3a+3=7 | | 2x-(3+x)= | | 4y^2+4y-28=0 | | 5z-4=8z-4z | | 9x+11-6x-2=2x+4+x+5 | | 2x^2-4x+22=0 | | 7c+18=-5c+78 |

Equations solver categories